Development of large bismuth absorbers for magnetic calorimeters applied to hard x-ray spectrometry - Rodrigues, Myriam; Pies, Christian; Fleischmann, Andreas; Enss, Christian (Journal of low temperature physics, 2014)
Bismuth is an interesting material for magnetic calorimeter absorbers applied to high energy resolution X-ray spectrometry; it has a low specific heat and high atomic number. However, past detector developments with Bi absorbers were confronted with the low thermal conductivity of bismuth that degraded the energy resolution and deformed the detector response function (non-Gaussian energy peak). In the present study, we have investigated the performances of large bulk bismuth absorbers ($$1× 1× 0.16$$1×1×0.16 mm$$^{3}$$3) thermally coupled to metallic magnetic sensors. Despite a very good baseline energy resolution, detectors with monolithic bismuth absorbers have degraded FWHM energy resolutions with any type of thermal coupling between the absorber and the sensor tested. In comparison tests with BiCu and BiAg bilayer absorbers demonstrated much better performances.